The Sabaic inscription A-20-216: a new Sabaean-Seleucid synchronism - Prioletta, Alessia (Proceedings of the Seminar for Arabian Studies, 2011)
The paper focuses on the unpublished inscription A-20-216, housed in the University Museum of Ṣanʿāʾ, which is a Sabaic votive text dedicated to the goddess Shams and to other South Arabian and foreign divinities and shares a number of traits in common with another Sabaic inscription housed in the British Museum, Ry 547. This text was discussed in the 2007 Seminar for Arabian Studies by Norbert Nebes, who suggested associating it with an unpublished fragment found in Maʾrib by the German Archaeological Institute. In the scholar's opinion the inscription, commissioned by inhabitants of Gerrha settled in South Arabia, might date back to the reign of King Seleucus I (end of the fourth century BC). The inscription at the University Museum of ṢanʿāʾJ now provides further proof of most of these hypotheses. In fact, it is written by one of the tribes mentioned in Ry 547 and contains the same dating formula, even if it gives a different year. Some of the foreign linguistic traits of Ry 547 are also shown in the text. From the point of view of South Arabian chronology, A-20-216 is even more important, as it offers a synchronism between Seleucus and a Sabaean king named Ydʿʾl Byn.